Dutch Military Agression in Batu-Pujon East Java 1947-1948: A Local History - Moch. Dimas Galuh Mahardika (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2022)
One of the events marking the period 1945-1950 was the Military Aggression I and II which deployed many military divisions in an effort to fight for independence in the regions. The Dutch' great desire to regain control of Indonesia after the proclamation is one form of real threat that must again be faced by the Indonesian nation. Under the pretext of “Police Action”, the Dutch soldiers carried out military activities while violating a previously agreed agreement. Turmoil in various regions began to appear, one of them in the Batu-Pujon region which is one of the highlands and flanked by several mountains. The status quo monument in Pandesari area became a symbol of the boundaries of dutch occupation and Republic territory. The battle that took place in the Batu-Pujon region was a small battle that took place during the Military Aggression. This article written by using the historical research methods try to explain the history of Dutch Military Agression in the local history context of Batu-Pujon region.